BACTERIOPHAGES: A NEW PARADIGM AND ADVANTAGES OVER ANTIBIOTICS IN MEDICAL PURPOSES - Вовк, О. О.; Бойченко, М. С.; Матвєєва, І. В.; Жук, О. В.; Бойченко, С. В. (Science-based technologies, 2017)
Comparative analysis of antibiotics and bacteriophages preparations properties. Substantiation of prospects of using bacteriophages in medical purposes. Methods: systematic analysis, analytical, monographic, synthesis, formalization, abstract and logical. Many years of antibiotics use for the treatment of various diseases has led to the emergence of multidrug-resistant bacterial strains. According to WHO, more than 60% of pathogens are resistant to major antibiotics, and in 10-20 years almost all will acquire antimicrobial resistance. The reasons for the rapid adaptation of microorganisms to antibiotics may include continual, unreasonable using of antibiotics for self-medication, and when they are not effective: URTI, cough, flu; the total use of antibiotics in agriculture to prevent the development of diseases that can be transmitted to humans through food; the ability of bacteria to mutate and adapt quickly to different antibacterial drugs; not complete course of antibiotics. In this situation, a decent alternative to antibiotics in the treatment of many diseases of bacterial origin can make bacteriophages opened nearly a century ago. The modern practice of applying bacteriophage preparations used for the prevention and treatment of infectious lesions of the gastrointestinal tract; purulent-inflammatory diseases of the eyes, ears, nose, mouth, throat, lungs; surgical infections; burn wounds; urogenital infections and other diseases. The main benefits of bacteriophages: selectivity; have no contraindications to use; do not cause the development of microbial resistance; have no toxic, allergic, and teratogenic effects; they can also be used in combination with other preparations, including antibiotics and probiotics.